KEBERADAAN SISTEM HAKIM KOMISARIS SEBAGAI ALTERNATIF PENGGANTI SISTEM PRAPERADILAN UNTUK MEMBERIKAN KEADILAN DAN KEPASTIAN HUKUM BAGI MASYARAKAT - Novriansyah Novriansyah; Conie Pania Putri (SOL JUSTICIA, 2022)
The Judge Commissioner system has the authority to decide or determine the validity of an arrest, detention, confiscation, termination of an investigation, termination of a prosecution which is not based on the principle of opportunity, and also to determine whether or not there is a need for detention, compensation or rehabilitation for a suspect or defendant who has been imprisoned illegally. legitimate. Another authority possessed by the Commissioner Judge is the determination of exceeding the time limit for an investigation or prosecution, and whether or not an examination of a suspect or defendant can be carried out without being accompanied by legal counsel. However, it is possible that the establishment of the Judge Commissioner system to replace the Pretrial system in the Criminal Procedure Code can create new problems. In this study, the author examines how the existence of the Judge Commissioner system as an alternative to the Pretrial system to provide justice and legal certainty for the community, how the provisions regarding the Commissioner Judge in the Bill on Criminal Procedure Law and what are the advantages and disadvantages compared to the Pretrial System. the author uses normative legal research or doctrinal legal research with a legal inventory approach, namely collecting norms that have been identified as legal norms. As a normative legal research, the data sources used are secondary data, consisting of primary, secondary and tertiary legal materials. Qualitative analysis of research data, namely comparing or applying applicable laws and regulations, opinions of scholars (doctrine) and other legal theories. The conclusion obtained in this writing is that with the existence of a Judge Commissioner system in the Draft Criminal Procedure Code in 2008 as a substitute for the Pretrial system, the presence of a Commissioner Judge is more effective than the Pretrial system which has many weaknesses and does not have a broader and detailed authority as contained in the Judge Commissioner system in Draft Criminal Procedure Code of 2008. The establishment of the Judge Commissioner system which has broad and more detailed duties and authorities is a refinement of Pretrial. So that with the Judge Commissioner system, the future Criminal Procedure Code can fulfill expectations to become a protector as well as a humanist (humane), transparent, and accountable (accountable) legal instrument or provide legal certainty, justice, and benefits for the community.